The coexisting state of the staggered flux and d-wave superconducting order in a t-J type model. (September 2019) - Fukuda, S; Yamazaki, K; Tsuchiura, H; Ogata, M
Abstract: We study the quasiparticle structures in the coexisting phase of the d-wave superconductivity (dSC) and the staggered flux state using the renormalized mean-field theory for the t - J type model with additional nearest-neighbor Coulomb repulsion V, based on the Gutzwiller approximation. We find that this coexisting state exhibits the dome-like behavior of dSC in the phase diagram and also the so-called two-gap structure found in ARPES experiments, both of which are quite consistent with the experimental results.